Adolescenza e disabilità: alcune annotazioni - Fratini, Tommaso (Studi sulla Formazione/Open Journal of Education, 2017)
The article deals with some considerations on adolescence in disability, in rela-tion to the new perspective of social inclusion. In this regard, both the full recog-nition and the right of the disabled person to have adolescence are included, as well as a differentiation of the implications of this phase of life in relation to the various forms of disability. Arguments on forms of disability with and without cognitive deficits are discussed, emphasizing the importance for the disabled teenager, for the purpose of his or her growth and maturation path, to develop se-cure attachment modes and rebel against the dictates of society and the culture of narcissism. In this light, the article closes with a pedagogical reflection on the concept of social inclusion, not as a mere acquiescent adaptation, but in relation to the need to implant new forms of a more solid social cohabitation.